Estruturas inteligentes aplicadas ao controle ativo de ruído de alta ordem em dutos - Nishida, Pedro Pio Rosa (2012)
In this study the possible use of smart structures for noise control in a higher order acoustic duct was considered. The best option for this control was the use of axial splitters in the duct in order to prevent higher order mode propagation. It is possible to perform the active noise control in each splitter section by using a single channel control system. The use of smart structures takes advantage of the splitter plate and uses it as the control source, which substitutes the traditional loudspeakers used in active noise control systems. In order to evaluate the possibility of the noise control using smart structures, an analytical model of a thin plate with piezoelectric actuators was built then the acoustic field generated by this vibrating structure inside of the duct was obtained. However, to obtain the acoustic field inside an splitted duct, a numerical method such as the Component Mode Synthesis has to be used. Using the equation of the acoustic field generated in the duct by the plate, it was possible to obtain the acoustic field inside the splitted duct. After that, the active noise control simulations for harmonic excitations were performed and the influence of the size of the plate excited by the PZT actuators was studied. Finally the active control for random noise was simulated, in which the number of actuators in the plate was changed. In conclusion, it is possible to say that the smart structures can be used in active noise control of ducts with splitters and the advantages and disadvantages of the conveyed technique were presented.